Estimate of induced stress during filling and discharge of metallic silos for cement storage (2015)
The present article show the structural analysis realized to metallic silo for storage cement through of the parametric model development in the finite element software ASNYS APDL, the fill and discharge pressures applied on the silo wall is determined with the Eurocode normative EN 1991-4.The model is development with type shell elements allowing that the structure silo fits to the cylindrical and conical geometric of the silo. It explains each of the phases having the development of the model and is made a detailed analysis of the results delivered by the software; different models are evaluated changing the sheet thickness for select the most appropriate. Also the results are analyzed when be changing the tilting the hopper and is reviewed the behavior of the silo when is analyzed with its structure. © The author; licensee Universidad Nacional de Colombia.